Data Warehouse Development for UPN “Veteran” Jakarta Library (Perancangan Data Warehouse pada Perpustakaan UPN “Veteran” Jakarta) - Henki Bayu Seta; Theresia Wati; Ika Nurlaili Isnainiyah (BBPSDMP KOMINFO MAKASSAR, 2017)
This article presents the design and development of data warehouse on UPN